ANALISIS SIFAT FISIS PADA RESERVOAR BATUPASIR MENGGUNAKAN METODE SEISMIK INVERSI IMPEDANSI AKUSTIK (AI) DAN MULTIATRIBUT PADA LAPANGAN “MNF” CEKUNGAN BONAPARTE - Muhammad Niko Febridon; Bagus Sapto Mulyatno; Egie Wijaksono (Engineering Faculty Universitas Lampung, 2018)
Analysis of the physical properties of the sandstone reservoir in this study was carried out using the acoustic impedance inversion method and seismic multi-attribute which was carried out at the Bonaparte Basin